2018
DOI: 10.1017/s0021932018000275
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Health and Socioeconomic Effects of Cousin Marriage in South Asia

Abstract: The effects of marriage between biological relatives on the incidence of childhood genetic illness and mortality are of major policy significance, as rates of consanguinity exceed 50% in various countries. Empirical research on this question is complicated by the fact that consanguinity is often correlated with poverty and other unobserved characteristics of households, which may have independent effects on mortality. This study has developed an instrumental variables empirical strategy to re-examine this ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…We were unable to evaluate consanguinity in 14 of the families in this study due to lack of parental DNA samples. However, the presence of homozygous pathogenic variants in our data is consistent with prior studies reporting an approximately 70% rate of consanguineous marriages in Pakistan (66)(67)(68). Nine of the 14 pathogenic variants identi ed have been previously reported (Table 2) (12,(14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 92%
“…We were unable to evaluate consanguinity in 14 of the families in this study due to lack of parental DNA samples. However, the presence of homozygous pathogenic variants in our data is consistent with prior studies reporting an approximately 70% rate of consanguineous marriages in Pakistan (66)(67)(68). Nine of the 14 pathogenic variants identi ed have been previously reported (Table 2) (12,(14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 92%
“…However, it is important to note that CM is religiously allowed in Islam but not encouraged [31,32]. As a Muslim-dominant country in South Asia, CM is practiced in Bangladesh [24,25,33]. However, the prevalence, causal factors, and genetic and reproductive consequences had not been studied thoroughly [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Thalassemia is highly concentrated in small towns where the consanguinity between relatives is more predominant and marrying close family members is a tradition in many countries including Iraq, leading to higher rates of genetic disorders (49). The latter investigation also reported that the frequency of genetic disorders among such children is around twice that in children of non-related parents (50,51). One billion people worldwide live in countries where marriage among relatives is common.…”
Section: Monhal Et Al (2012) (22) Andmentioning
confidence: 99%
“…One billion people worldwide live in countries where marriage among relatives is common. Of this billion, one in three is married to a second cousin or closer relative or is the progeny of such a marriage (50,51). In Iraq, the consanguinity is still widely spread and predominant (52) and some areas showed consanguinity in around 60% of all marriages (53).…”
Section: Monhal Et Al (2012) (22) Andmentioning
confidence: 99%